The adapted changes of abstract article vegetative organs of grinding tuber Dioscoreae persimilis Prain et Burkill growing in North Vietnam - Lan Huong, Do Thi; Ba, Tran Van (Academia Journal of Biology, 2012)
Grinding tuber’s patterns (Dioscoreae persimilis) collected at four different research areas show dapted differences in their morphology and anatomy. In plants growing in high mountainnoeus areas, the more angles of grinding tuber’s stems increase, while the diameter and the length of their stems and internodes (the distance between two leaf nodes) decrease. Cross-sectional slices of the trunk observed on the microscope with cross sections of four samples are rather different and coincide to the external morphology observed. Whereas in plants growing in low lands, the more angles of stems increase. The conduct system with 6-8 large vascular bundles, 6-9 small vascular bundles arranged alternately (on the same circle with a fulcrum is a round of sclerenchyma) or arranged in two circles, between bundles are large spaces which help stems to have flexible structure. Grinding tuber (Dioscoreae persimilis) is a preferred light tree having a thick layer of cuticle, numerous stomata, palisade tissues and spongy tissues are rich in layers.